Optimalisasi Proses Pembelajaran Inovatif Melalui Pelatihan Perancangan Game Edukasi Berbasis Kecerdasan Buatan Menggunakan Scratch - Chotijah, Umi; Bhakti, Henny Dwi; Putri, Erna Dwita Sari Cahyani; Akbar, Muhammad Asad Muhibbin; Fahmi, Yusril (Forum Kerjasama Pendidikan Tinggi, 2026)
Community service activities were carried out to address the problem of low utilization of interactive technology in mathematics learning at SMA Muhammadiyah 5 Digital Content Class, Padang Bandung, Dukun District, Gresik Regency. The purpose of this activity is to improve the competence of teachers and students in designing innovative learning media thru the development of artificial intelligence-based educational games. The implementation methods include workshops, hands-on practice, group discussions, and intensive mentoring. Participants are trained to design game flow, integrate simple artificial intelligence concepts, and apply mathematical logic in Scratch. The evaluation results show an average increase of 35.8% in participants' knowledge scores between the pre-test and post-test. Additionally, based on the satisfaction survey given to teachers and students. From 92% of teachers who felt the training was very beneficial for the development of their teaching skills, and 88% of students stated that this activity was fun and made them more interested in learning mathematics, showing high enthusiasm and being able to produce educational game prototypes relevant to mathematical material. This activity is expected to serve as a model for sustainable training in optimizing the use of artificial intelligence-based technology for more engaging and practical mathematics learning.